2017
DOI: 10.5194/pb-4-9-2017
|View full text |Cite
|
Sign up to set email alerts
|

Detection systems for antibody responses against herpes B virus

Abstract: Abstract. Herpes B virus (BV) infection is highly prevalent among adult Asian macaques and rarely causes severe disease in infected animals. In contrast, BV infection of humans can induce fatal encephalitis in the absence of treatment. Therefore, the development of diagnostic tests for specific and sensitive detection of antibodies against BV is an important task. The cross-reactivity of antibodies against BV with related simplex viruses of other primates may afford an opportunity to obtain sensitive detection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Here, we used a chip-based platform to analyze macaque colonies for the presence of blood serum antibodies against eight NHP viruses (SRV/D, SIV, STLV, SFV, BV, CMV, LCV, RRV) and a human virus (MV) that constitutes a threat to NHPs and human health. Our results indicate that infection with the herpesviruses CMV, RRV and LCV as well as the retrovirus SFV is frequent in the animal population studied and suggest that previous efforts, based on testing with in-house assays for BV-specific antibodies (Pöhlmann et al, 2017), to establish a BV-free colony were successful. Finally, our results suggest a potential transmission of MV to NHPs enrolled in research programs that involve frequent animal-human contact, although the unknown MV vaccination status of the NHPs in question precludes solid conclusions.…”
Section: Discussionmentioning
confidence: 57%
See 4 more Smart Citations
“…Here, we used a chip-based platform to analyze macaque colonies for the presence of blood serum antibodies against eight NHP viruses (SRV/D, SIV, STLV, SFV, BV, CMV, LCV, RRV) and a human virus (MV) that constitutes a threat to NHPs and human health. Our results indicate that infection with the herpesviruses CMV, RRV and LCV as well as the retrovirus SFV is frequent in the animal population studied and suggest that previous efforts, based on testing with in-house assays for BV-specific antibodies (Pöhlmann et al, 2017), to establish a BV-free colony were successful. Finally, our results suggest a potential transmission of MV to NHPs enrolled in research programs that involve frequent animal-human contact, although the unknown MV vaccination status of the NHPs in question precludes solid conclusions.…”
Section: Discussionmentioning
confidence: 57%
“…A commercial chip-based screening system was used to detect antibodies against SRV/D, SIV, STLV, SFV, BV, CMV, RRV, LCV and MV. The animals had previously been tested negative for BV antibodies using in-house assay systems Male 74 (32.0) 0.0 (0) 0.0 (0) 0.0 (0) 0.0 (0) 13.5 10 Infant 4 (1.7) 0.0 (0) 0.0 (0) 0.0 (0) 0.0 (0) 0.0 (0) 75.0 (3) 100 (4) 100 (4) 50.0 (2) Juvenile 37 (16.0) 0.0 (0) 0.0 (0) 0.0 (0) 0.0 (0) 0.0 (0) 94.6 (35) 91.9 (34) 73.0 (27) 78.4 (29) Adolescent 47 (20.4) 0.0 (0) 0.0 (0) 0.0 (0) 0.0 (0) 0.0 (0) 97.9 (46) 83.0 (39) 78.7 (37) 100 (47) Adult 104 (45.0) 0.0 (0) 0.0 (0) 0.0 (0) 1.9 (2) 10.6 (11) 100 (104) 90.4 (94) 92.3 (96) 98.1 (102) Aged 39 (16.9) 0.0 (0) 0.0 (0) 5.1 (2) 10.3 4 (Pöhlmann et al, 2017) and were also found to be negative employing the commercial detection system (Table 1). Similarly, all animals were negative for SIV antibodies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations